Gain-Reconfigurable Hybrid Metal-Graphene Printed Yagi Antenna for Energy Harvesting Applications - Alex-Amor, Antonio; Palomares-Caballero, Ángel; De la Fuente, Elena; Muriel-Barrado, Alfonso; Valenzuela-Valdés, Juan Francisco; Fernández-González, José M.; Padilla, Pablo (My University, 2019)
This paper presents a hybrid metal-graphene printed Yagi antenna with reconfigurable gain that operates in the 5.5-GHz band. The balun and the driven elements are made of copper, while the directors are made of graphene. The graphene acts as a tunable material in the design. By switching the conductivity of the graphene, it is achieved a similar effect to adding or subtracting directors in the antenna. Hence the gain of the printed Yagi can be easily controlled. This could be of special interest in RF energy harvesting in the design of reconfigurable harvesting elements.
Keywords: Grafeno; Energía - Almacenamiento; Graphene; Yagi antenna; Tunable material; Energy harvesting; Reconfigurability